Ways of the Word : Learning to Preach for Your Time and Place - Brown, Sally A. (Sally Ann); Powery, Luke A., 1974- (Book collections on Project MUSE., 2016)
Preaching, and the discipline of preaching, is at a crossroads. The changing realities of church and theological education, the diversity of our classrooms, and our increasingly complex community contexts leave us in search of tools to help train a rising generation of preachers for a future whose contours are far from clear. The questions are immense: How to support preachers in contexts that are diverse religiously, culturally, and ethnically, both inside and outside the church? How to help students take varied contexts seriously as they are formed as leaders? In Ways of the Word, a dynamic team of master preachers brings much-needed help. Different in race, gender, age, and tradition, both Sally A. Brown and Luke A. Powery speak with one voice their belief that preaching is-Spirit-empowered event: an embodied, vocalized, actively received, here-and-now witness to the ongoing work of God in the world. They aspire to help students and preachers alike to reflect on a journey of learning by doing. They aim to help preachers to become more attuned to the Spirit, more adept in preaching's component skills, and more self-aware about all that is at stake in proclaiming the redemptive work of God in specific contexts.